REVIEWS - Rooke, Deborah W. (Journal of Semitic studies, 2003)
History and Ideology in the Old Testament: Biblical Studies at the End of a Millennium (The Hensley Henson Lectures for 1997) JamesBarr . Oxford University Press, Oxford , 2000. Pp. viii + 198. Price: £25.00 . ISBN: 0-19-826987-0.